Disparity of Regional Developments Between Service Center Functions in North Aceh Regency - Shiddiq, Wafi; Muliadi, Muliadi; Gunawan, Arief (Perencanaan Wilayah dan Kota FT UB, 2025)
North Aceh Regency recorded the highest unemployment rate in Aceh Province in 2020, highlighting a critical disconnect between regional planning and socio-economic reality. This study aims to analyze the hierarchy of regional development and the level of disparity among service center functions, ranging from National Activity Centers (PKN) to Regional Service Centers (PPK). Utilizing a quantitative descriptive approach, this research employs Scalogram analysis to determine the Regional Development Index based on socio-economic, demographic, and accessibility variables. Additionally, the Williamson Index is applied to quantify income disparity using Gross Regional Domestic Product (GRDP) per capita data from 2011 to 2020. The research results indicate that among the 27 sub-districts in North Aceh Regency, the highest level of regional development between 2011 and 2020 was observed in the Tanah Luas sub-district. This signifies a significant shift in the spatial structure: Tanah Luas emerged as a new high-growth center, while the administrative capital, Lhoksukon, experienced a relative decline in its development index. Furthermore, disparity analysis reveals that while inequality in the hinterland (e.g., Cot Girek) has normalized, economic polarization has intensified in industrial enclaves like Muara Batu. These findings provide empirical evidence for the necessity of targeted policy interventions, advocating for a shift from a purely growth-oriented model to one that prioritizes spatial equity and the revitalization of lagging hinterlands.